(untitled) (Journal of Science and Technology, 2016)
From January 1988 to July 1992 cervical smears were taken from a total of 4053 women at the Catholic Hospital at Battor in the Tongu District of the Volta Region of Ghana. Staining, grading and classification of the slides were deo according to the Papanicolaou ’s method. Three thousand nine hundred and thirty-three (97.04%) of the smears taken were negative, 67 (1.65%) were suspicious and 53 (1.31%) were positive. There were no positive findings among women below the age of 24 years. Of the positive results the highest prevalence was among women in age group 50 and above (58.49%), grand multiparae of parity 5 and above (62.26%), and rural dwellers (37.74%). Cervical intraepithehal neoplasia has also been shown in other studies to be related to advanced age, high parity and rural residence and women with lower socio-economic status. Mass population screening for pre-invasive cervical cancer may not yet be feasible and cost-effective in our population because of other priority health needs. However, selective screening of those women at highest risk, namely women of advanced ageing high parity and low socio-economic status is advisable as a preventive measure against later development of invasive cervical carcinoma. Recommendations are made for the establishment of a selective cervical cancer screening program in Ghana.